Adsorption and photocatalytic removal of dimethylarsenic acid using titania and zinc oxide thiol functionalized ZSM-5 zeolite - Sulaiman, Nur Nadira (2015)
This research is to correlate physicochemical properties of metal oxides-ZSM-5 functionalized thiol with their catalytic properties towards adsorption and photocatalytic removal of dimethylarsenic acid (DMA). TiO2 and ZnO were attached on the surface of the ZSM-5 zeolite by impregnation. The impregnation of these metal oxides were carried out on the surface of the ZSM-5 followed by modification of functional group on ZSM-5 surfaces with thiol to form TiO2 impregnated ZSM-5 functionalized with thiol (TiO2-ZSM5-SH) and ZnO impregnated ZSM-5 functionalized with thiol (ZnO-ZSM5-SH). Characterizations by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance ultraviolet-visible spectroscopy (DR UV-Vis) and energy dispersive X-ray (EDX) proved that the metal oxides were successfully attached on the surface of the ZSM-5. It was demonstrated that the modification of functional group on ZSM-5 surface with thiol was also successful. Images from high-resolution transmission electron microscope (HRTEM) and scanning electron microscope (SEM) showed TiO2-ZSM5-SH and ZnO-ZSM5-SH appeared as crystalline agglomerated particles. TiO2-ZSM5-SH had shown better performance in the photocatalytic removal of DMA by 49% compared to 41% removal by ZnO-ZSM5-SH. On the contrary, TiO2-ZSM5-SH gave lower percentage in the adsorption of DMA which was 23% as compared to 36% with ZnO-ZSM5-SH. Results showed that TiO2-ZSM5-SH and ZnO-ZSM5-SH possess photocatalytic properties. The percentage removal of DMA had increased to 49% for TiO2-ZSM5-SH and 41% for ZnO-ZSM5-SH compared to the use of bare TiO2 (20%) and ZnO (23%). These proved that thiol functionalization on ZSM-5 enhanced the ability of both materials to remove DMA.